The Holy Scripture and its role in the development of the personality of believers - Ghiuță, Ștefan-Adrian (Technium Social Sciences Journal, 2022)
The explanation of Scripture essentially coincides with the application of its content, with the passage of this content into human life through the foundation of the Church, with the concrete specification of its structures, hierarchically, sacramental based on the indications of the Lord. Thus, Scripture passes into Tradition, which is essentially nothing more than the content of Scripture, applied to human life. A seed of redemption, the Old Testament is fulfilled by the New Testament in which the figure of the Savior and his redemptive deeds can be the most appropriate guide for the Christian’s life. But we cannot ignore the divine message of the Word of God that comes to perfect justice through love, through deeds that no longer pour out mercy and charity only on a community but on all humanity.